Cyclic loading testing of repaired SMA and steel reinforced concrete shear walls. (1st August 2018) - Cortés-Puentes, Leonardo; Zaidi, Mohammed; Palermo, Dan; Dragomirescu, Elena
Highlights: Testing of repaired concrete shear walls reinforced with steel and SMA is presented. The repair strategy recovered the strength and stiffness of the original walls. The repaired walls dissipated more energy than the original walls. The repaired SMA wall recovered the imposed lateral displacements up to 2% drift. The repair with SMA bars reduced the rotations and shear strains of the SMA wall. Abstract: This paper presents the results of reverse cyclic load testing of a repaired slender concrete shear wall reinforced internally with superelastic Shape Memory Alloys (SMAs) in the boundary zones within the plastic hinge region. In addition, a companion-repaired wall reinforced with deformed mild steel was also tested. Provided herein is an assessment of the performance of the repaired walls against the same set of walls previously tested in their original condition. The repair strategy included removing heavily damaged concrete within the plastic hinge region, replacing ruptured and buckled reinforcing steel, and shortening of the SMA bars in the boundary zones. High-strength, self-consolidating concrete replaced the removed concrete. The concrete above the plastic hinge region remained intact given the negligible damage (hairline cracking) of the original walls in this zone. The test results demonstrated that SMA-reinforced concrete structural components are self-centering, permitting repair of damaged areas. Furthermore, the SMA bars were re-usable for the repair application due to their capacity to reset to their original state within the range of inelastic strains of up to 6%. The repaired walls were capable of restoring the yield and ultimate lateral load capacities, but sustained lower drift capacities. The repaired SMA wall was capable of recovering the imposed lateral drifts up to 2%, after which residual displacements accumulated due to rupturing of the SMA bars in the boundary zone. The repaired walls dissipated up to 7.8% more energy than their original walls for a significant portion of the loading range. The length of the SMA bars and the presence of starter bars in the original walls were influencing factors in the location of failure of the SMA- and steel-reinforced walls.